In vitro Multistage Malaria Transmission Blocking Activity of Selected Malaria Box Compounds - Malebo HM; D'Alessandro S; Ebstie YA; Sorè H; Tenoh Guedoung AR; Katani SJ; Parapini S; Taramelli D; Habluetzel A (Dove Medical Press, 2020)
Hamisi M Malebo,1 Sarah D’Alessandro,2,3 Yehenew A Ebstie,4 Harouna Sorè,5 Alain R Tenoh Guedoung,4 Shaaban J Katani,1 Silvia Parapini,2,3 Donatella Taramelli,3,6 Annette Habluetzel3,4 1Department of Traditional Medicine Research, National Institute for Medical Research, Dar es Salaam, Tanzania; 2Dipartimento di Scienze Biomediche per la Salute , University of Milan, Milan, Italy; 3Centro Interuniversitario di Ricerca Sulla Malaria/Italian Malaria Network, University of Milan, Milan, Italy; 4School of Pharmacy, University of Camerino, Camerino, Italy; 5Centre National de Recherche et de Formation sur le Paludisme (CNRFP), Ouagadougou, Burkina Faso; 6Dipartimento di Scienze Farmacologiche e Biomolecolari, University of Milan, Milan, ItalyCorrespondence: Hamisi M MaleboDepartment of Traditional Medicine Research, National Institute for Medical Research, Postal Box 9653, Dar es Salaam, TanzaniaTel +255 22 2121400Fax +255 22 2121360Email hmalebo@gmail.comSilvia ParapiniDipartimento di Scienze Biomediche per la Salute, University of Milan, Via Pascal 36, 20133, Milan, ItalyTel +39 02 3031 5082Fax +39 02 5031 5093Email silvia.parapini@unimi.itPurpose: Continuous efforts into the discovery and development of new antimalarials are required to face the emerging resistance of the parasite to available treatments. Thus, new effective drugs, ideally able to inhibit the Plasmodium life-cycle stages that cause the disease as well as those responsible for its transmission, are needed. Eight compounds from the Medicines for Malaria Venture (MMV) Malaria Box, potentially interfering with the parasite polyamine biosynthesis were selected and assessed in vitro for activity against malaria transmissible stages, namely mature gametocytes and early sporogonic stages.Methods: Compound activity against asexual blood stages of chloroquine-sensitive 3D7 and chloroquine-resistant W2 strains of Plasmodium falciparum was tested measuring the parasite lactate dehydrogenase activity. The gametocytocidal effect was determined against the P. falciparum 3D7elo1-pfs16-CBG99 strain with a luminescent method. The murine P. berghei CTRP.GFP strain was employed to assess compounds activities against early sporogonic stage development in an in vitro assay simulating mosquito midgut conditions.Results: Among the eight tested molecules, MMV000642, MMV000662 and MMV006429, containing a 1,2,3,4-tetrahydroisoquinoline-4-carboxamide chemical skeleton substituted at N-2, C-3 and C-4, displayed multi-stage activity. Activity against asexual blood stages of both strains was confirmed with values of IC50 (50% inhibitory concentration) in the range of 0.07– 0.13 μM. They were also active against mature stage V gametocytes with IC50 values below 5 μM (range: 3.43– 4.42 μM). These molecules exhibited moderate effects on early sporogonic stage development, displaying IC50 values between 20 and 40 μM.Conclusion: Given the multi-stage, transmission-blocking profiles of MMV000642, MMV000662, MMV006429, and their chemical characteristics, these compounds can be considered worthy for further optimisation toward a TCP5 or TCP6 target product profile proposed by MMV for transmission-blocking antimalarials.Keywords: Plasmodium, multi-stage antimalarials, transmission blocking drugs, malaria elimination